Pathophysiological Prerequisites and Therapeutic Potential of Fecal Microbiota Transplantation in Severe Alcoholic Hepatitis - D. V. Garbuzenko (Архивъ внутренней медицины, 2022)
Due to the high morbidity and mortality, the problem of severe alcoholic hepatitis has not lost its relevance to date. In the absence of specific therapy, the associated to him one-month survival rate is low, and mortality rates reach 30-50 %. Although the use of corticosteroids is a scientifically proven first-line treatment for severe alcoholic hepatitis, a short-term response is observed in approximately 60 % of patients with no long-term survival benefits compared to placebo. It should also take into account the occurrence of adverse side reactions to their use in about 50 % of patients, as well as the risk of complications, in particular, bacterial and fungal infections. The second-line drugs, for example, pentoxifylline, etanercept, infliximab, N-acetylcysteine, etc. in severe alcoholic hepatitis did not show an improvement in the clinical outcome. The modern guidelines discuss the feasibility of liver transplantation in carefully selected patients who do not respond to corticosteroid treatment with severe alcoholic hepatitis. Nevertheless, due to numerous contradictions, it is too early to talk about the introduction of this approach into clinical practice. In recent years, some progress has been made in understanding the pathophysiological mechanisms of the development of alcoholic hepatitis, which served as an impetus for new directions of its pathogenetic therapy. One of them is the techniques that provide intestinal eubiosis, in particular, through the fecal microbiota transplantation. The purpose of the review was to describe the pathophysiological prerequisites and therapeutic potential of fecal microbiota transplantation from healthy donors to patients with severe alcoholic hepatitis. Experimental studies have shown a positive effect of fecal microbiota transplantation on the intestinal microflora, which led to a weakening of alcohol-induced liver damage. In patients with severe alcoholic hepatitis, it improved the severity of its symptoms and contributed to increased survival compared to those receiving corticosteroids. These preliminary results are encouraging and create conditions for further clinical trials involving a large cohort of patients with severe alcoholic hepatitis, which will allow us to identify those for whom fecal microbiota transplantation will be most effective with minimal risk of complications.